A20 Controls Macrophage to Elicit Potent Cytotoxic CD4+ T Cell Response - Wang, Lifeng; Hong, Bangxing; Jiang, Xiaoxia; Jones, Lindsey; Chen, Si-Yi; Huang, Xue F. (PLOS ONE, 2012)
Emerging evidence indicates that CD4+ T cells possess cytotoxic potential for tumor eradication and perforin/granzyme-mediated cytotoxicity functions as one of the important mechanisms for CD4+ T cell-triggered cell killing. However, the critical issue is how the cytotoxic CD4+ T cells are developed. During the course of our work that aims at promoting immunostimulation of APCs by inhibition of negative regulators, we found that A20-silenced Mф drastically induced granzyme B expression in CD4+ T cells. As a consequence, the granzyme-highly expressing CD4+ T cells exhibited a strong cytotoxic activity that restricted tumor development. We found that A20-silenced Mф activated cytotoxic CD4+ T cells by MHC class-II restricted mechanism and the activation was largely dependent on enhanced production of IFN-γ.